APAKAH GENAI MENINGKATKAN 4C? SEBUAH STUDI DI KALANGAN MAHASISWA PENDIDIKAN TINGGI - Nadya Eka Samudra Pratiwi; Achmad Virgi Ardian Febrianto; Yuta Afiyanto Ramandani; Erlyn Ayu Natali; Moch. Hamzah Rofiulloh; Irena Yolanita Maureen (EDUPEDIA, 2025)
This study aims to examine empirically the influence of perceived usefulness of Generative Artificial Intelligence (GenAI) and teaching method on students’ 4Cs skills (critical thinking, creativity, communication, and collaboration) in higher education. The research also investigates the mediating role of teaching method in the relationship between perceived usefulness of GenAI and 4Cs competencies. The object of this research involved 50 undergraduate students from Universitas Negeri Surabaya, Indonesia. Data were collected through a structured questionnaire consisting of three main constructs, namely perceived usefulness of GenAI, teaching method, and 4Cs skills, measured using a five-point Likert scale. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that perceived usefulness of GenAI does not have a significant direct effect on students’ 4Cs skills. However, perceived usefulness of GenAI significantly influences teaching method, and teaching method shows a strong and significant effect on 4Cs development. Furthermore, teaching method does not significantly mediate the relationship between perceived usefulness of GenAI and 4Cs. These findings suggest that GenAI technology alone is not sufficient to enhance students’ 21st-century skills without strong pedagogical integration. Teaching method is confirmed as the key factor that directly contributes to the development of critical thinking, creativity, communication, and collaboration among students. Therefore, higher education institutions are encouraged to prioritize instructional innovation and pedagogical strategies to maximize the potential benefits of GenAI for meaningful learning and skills development. The study contributes to the extension of the Technology Acceptance Model (TAM) by highlighting the importance of pedagogical design beyond technological perception in improving learning outcomes.